Promoting Inclusion Using OER in Vocational Education and Training Programs - Baldiris, Silvia; Mancera, Laura; Licona, Levintón; Avila, Cecilia; Bacca, Jorge; Politis, Yurgos; Goodman, Lizbeth; Treviranus, Jutta (Lecture Notes in Computer Science, 2020)
Open Educational Resources (OER) have been declared by UNESCO as a promising tool to address inclusion in educational settings. However, recent studies support the need to pay more attention to the accessibility and inclusion capacity of OER. In this context, this paper provide evidence about the benefits of adopting Universal Design for Learning and the Web Content Accessibility Guidelines to support the OER creation considering the variability of students in Vocational Education and Training (VET) programs. For doing so, it was created some OER using CO-CREARIA model and it was validated on VET setting in Colombia. Results evidence that the OER created support the achievement of high level of motivation and academic performance.
Ponencia de la conferencia "18th International Conference on Advances in Web-Based Learning, ICWL 2019; Magdeburg; Germany; 23 September 2019 through 25 September 2019"
Keywords: accessibility; co-creation; inclusion; Open Educational Resource; universal design for learning; Scopus(2); WOS(2)